IT-driven business models global case studies in transformation - Kagermann, Henning. (Wiley, 2010)
"This book will show organizations how business model innovation should be a key focus area in today's global economy. It features cases from businesses around the globe who have developed their own business models to acheive high levels of performance and interviews from key executives. A primary focus in the book will be on the role of technology in driving and enabling changes to fundamental facets of a business. Business model innovation is occuring around the world, in essentially every industry and in processes ranging from R&D to M&A, supply chain, and marketing. Case examples will be included from ABB, IKEA, Apple, Tata, SHARP, Daudi Aramco, DeBeers, Telefonica, Valero Energy, LEGO, Proctor & Gamble, among others"--